A first-principles investigation of a new hard multi-layered MnB2 structure. Issue 17 (7th February 2017) - Xu, Chunhong; Bao, Kuo; Ma, Shuailing; Ma, Yanbin; Wei, Shuli; Shao, Ziji; Xiao, Xuehui; Feng, Xiaokang; Cui, Tian
Abstract : A novel high-pressure phase of multi-layers Immm -MnB2 is confirmed on the convex hull diagram of the Mn-B systems at 50 GPa (b). Abstract : ReB2 -type MnB2 has always been considered to be the ground-state structure of MnB2 . However, subsequent theoretical study has revealed that this structure is easy to decompose into elemental Mn and B under ambient conditions, which motivated us to look for a stable MnB2 structure at high pressures. Using structure prediction algorithm USPEX and density functional theory calculations, we found a stable multi-layered MnB2 structure with space group Immm at high pressure. The calculated hardness of Immm -MnB2 is 22.5 GPa, which makes it a potential hard multifunctional material along with its conductive and magnetic properties. The hexagonal graphene-like boron networks of Immm -MnB2 contribute to its hardness and stability.